Decellularized Cartilage Microparticles: Dissociated and Reconstituted Cartilage Microparticles in Densified Collagen Induce Local hMSC Differentiation (Adv. Funct. Mater. 30/2016). (8th August 2016) - Novak, Tyler; Seelbinder, Benjamin; Twitchell, Celina M.; Voytik‐Harbin, Sherry L.; Neu, Corey P.
Abstract : On page 5427, C. P. Neu and co‐workers report on successfully combining the benefits of native tissue biochemistry/structure with the tunability of reconstituted biomaterials for the formation of clinically relevant tissue composites. Native articular cartilage and reconstituted type I collagen form a moldable 'cartilage clay' that can be custom designed to meet the mechanical, biochemical, and geometric needs of a clinical implant; showing the capability to locally differentiate progenitor cells.